A new introduction to modal logic - Hughes, G. E. (George Edward), 1918- (Routledge, 1996)
This entirely new work guides the reader through the most basic systems of modal propositional logic up to systems of modal predicate with identity, dealing with both technical developments and discussing philosophical applications.